Calamus himalayanus is a new synonym of C. flagellum (Arecaceae) - Mehmud, Selim; Roy, Himu (Phytotaxa, 2025)
In India, the species Calamus flagellum Griffith ex Walpers (1852: 484) is mainly confined in northeastern states (Henderson 2020) and West Bengal (Henderson 2009, Renuka et al. 2010, Renuka & Sreekumar 2012). It is known for its long flagellum, which was measured up to 7 m or more (Beccari 1908). This species is morphologically highly variable (Evans et al. 2002, Renuka & Sreekumar 2012) and along with India, it is distributed in Bangladesh, China (southern), Myanmar (northern), Thailand (northern), Laos (northern), Tibet, and Vietnam (north and central) (Henderson 2020). Under C. flagellum, two varieties were proposed based on variations in morphological characters, but later studies revealed insufficiency and inconsistency of the features in support of these varieties. The variety C. flagellum var. karinensis Beccari (1908: 129) was established based on the spines of leaf sheath and rachis, multiple short spikelets, and fruit scales, which was raised to C. karinensis (Beccari) Pei Sheng-Ji & Chen San-Yang (1989: 133), but Evans et al. (2002) merged it under C. flagellum. Another variety, C. flagellum var. furvifurfuraceus S.J.Pei & S.Y.Chen (1989: 133) was established based on the grouped leaflets, brown indumentum in rachis and sheath, and small fruit (Pei et al. 1989, Evans et al. 2002) and it was also merged under C. flagellum (Henderson 2020).